Intravenous paraoxon (POX) exposure: coagulation studies in mini pigs - Petroianu, Georg; Toomes, Mia; Maleck, Wolfgang; Bergler, Wolfgang; Rüfer, Roderich (Chemico-biological interactions, 1999)
The in vivo effects of the organophosphorus compound (OPC) paraoxon (POX) on blood coagulation of mini pigs were assessed by measuring the partial thromboplastin time (PTT), prothrombin time (PT), fibrinogen, factor V, factor VII, factor VIII, antithrombin III, protein C, and platelet count. The mini pigs were randomly assigned to a POX-treatment group (n=9) receiving 54 mg POX kg−1BW−1 or the control group (n=9). Measurements were carried out over a period of 150 min after poisoning. The exposure to POX did not have any influence on measurements of PT, factor VIII, factor VII, factor V, antithrombin III, protein C, or fibrinogen compared to the control group evaluated by rank order test (ROT) during the time of observation (150 min). Changes seen in the intrinsic coagulation followed a biphasic pattern corresponding to an early sympathomimetic phase with PTT-shortening and a decrease of the platelet count, and a late vagal phase, with PTT-prolongation. The hypercoagulability seen in the sympathomimetic phase is probably due to a massive release of catecholamines from the adrenals. Previous studies showed in vitro no coagulation activating effect of POX. The hypocoagulability in the vagal phase shown by the PTT-prolongation is probably due to POX influencing platelet function or its inhibition of clotting factors, which are serine proteases, or a combination of the two.